Surgical approach for kidney transplantation under spinal anesthesia. Issue 12 (31st December 2020) - Nawabi, Atta; Sullivan, Peter; De Ruyter, Martin; Pichoff, Amy; King, Clay D; Nawabi, Perwaiz
Abstract: Kidney transplantation is the treatment of choice for patients with end-stage renal disease (ESRD). It has been shown to improve quality of life as well as extending life of patients with ESRD as compared to renal replacement therapy (5-year survival rate of 68% after transplant vs 36% dialysis) (Hart A, Smith JM, Skeans MA. OPTN/SRTR 2015 annual data report: kidney. Am J Transplant 2017;17:21–116). Traditionally, patients undergo general endotracheal tube anesthesia for this surgery. During the COVID-19 pandemic, general anesthesia drugs and airway equipment were in short supply. Additionally, airway manipulation was avoided when possible due to concern for virus spread from aerosolizing procedures (i.e. intubation/extubation). In this case report, we review a 65-year-old female with an ESRD due to hypertension and diabetes that underwent deceased donor kidney transplant under spinal anesthesia. We will further discuss the benefits of spinal anesthesia in renal transplant operations.